2016
DOI: 10.1007/s11255-016-1333-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between PAI-1 4G/5G polymorphism and diabetic nephropathy: a meta-analysis in the Chinese population

Abstract: This meta-analysis showed that the PAI-1 4G/4G variant, 4G allele might be risk alleles for DN susceptibility in the Chinese population, and further studies in other ethic groups are required for definite conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
7
1
1
Order By: Relevance
“…Concerning the association with DN risk, our results indicated a strong linkage between SERPINE1 4G polymorphism and DN risk in the overall and Asian populations. This is consistent with former studies [ 25 , 71 ] and further implies that heterogeneity is affected by ethnicity. Moreover, insufficient genetic data in mix ethnicities could limit the possibility of further discussion regarding this population, which to a considerable extent could alter the overall analyses.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the association with DN risk, our results indicated a strong linkage between SERPINE1 4G polymorphism and DN risk in the overall and Asian populations. This is consistent with former studies [ 25 , 71 ] and further implies that heterogeneity is affected by ethnicity. Moreover, insufficient genetic data in mix ethnicities could limit the possibility of further discussion regarding this population, which to a considerable extent could alter the overall analyses.…”
Section: Discussionsupporting
confidence: 93%
“…Chang et al (4) stated that the homozygous 5G allele in the PAI gene rs1799889 polymorphism was defined as a protective factor in the development of diabetes in obese diabetic and insulin resistance patients. In a meta-analysis study, it was shown that the PAI-1 4G allele could be a risk allele for DN sensibility in the Chinese population (18). Unlike our results, Chen et al (19) reported that the PAI-1 rs1799889 polymorphism was not associated with T2 DM risk.…”
Section: Discussioncontrasting
confidence: 94%
“…14 It is advised to enrol enough number of samples to decipher the genotypes frequency of a population: we have enrolled a higher number of healthy females (n = 350) compared to earlier studies. 14 PAI-1 down regulates fibrinolysis and maintains the appropriate plasminogen plasmin ratio. The role of PAI-1 in human osteoporosis is ill defined.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports including healthy subjects from Fujian and Shandong showed a higher prevalence of 5G/5G genotype over wild-type (4G/4G) and heterozygous mutants (4G/5G). 14 It is advised to enrol enough number of samples to decipher the genotypes frequency of a population: we have enrolled a higher number of healthy females (n = 350) compared to earlier studies. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation